Paradigma Kalam Dalam Konservasi Lingkungan Menurut Said Nursi - Nur Hadi Ihsan; Moh. Isom Mudin (Tasfiyah: Jurnal Pemikiran Islam, 2020)
This research departs from the fact that environmental conservation efforts are increasingly needed due to natural damage that increases continually. However, the instrumental and social efforts performed by the environmental activists are still partial and have not touched the fundamental aspects. Islam as a Religion and basis of comprehensive science could resolve this aspect.  Rasa’il Nur, a masterpiece written by Sa’id Nursi supposed to offers a solution to the problem.  This study aims to reveal the environmental conservation paradigm by Sa'id Nursi and find a new direction based on Islamic environmental conservation. This research is a literature study, qualitative models and figure studies, using critical-reflective analysis, with a kalam perspective. Nursi views the strong relationship of Tauhid (monotheism) and nature. Tauhid (monotheism) is the principle understanding to see the ecological elements which he calls the "God’s Sign". Human is supposed to see nature with the paradigm of 'harfi' instead of 'ismi'. The paradigm of ‘ismi’ which denied the divine value behind nature could be a reason for the environmental damage. As for ‘harfi’ perspective, the nature was inseparable from the divine’s side. The physical form of nature and its diversity are the visible book (kitab mandzur) and beautiful cosmos (syari’ah kauniyyah). Nature is a manifestation of ‘asma-ul khusna’, including the names ‘al-jalal’, ‘al jamal’ and ‘al quddus’. All ecological elements move and worship based on ‘mahabbah’. With these basics, Nursi denounced acts of destruction against nature.